Cortical encoding of linguistic constituent with and without morphosyntactic cues. (August 2020) - Chang, Claire H.C.; Dehaene, Stanislas; Wu, Denise H.; Kuo, Wen-Jui; Pallier, Christophe
Abstract: This study examined the brain areas involved in combining words into larger units when there are few or no morphosyntactic cues. We manipulated constituent length in word strings of the same length under two conditions: Mandarin sentence, which had sparse morphosyntactic cues, and nominal phrase that had no morphosyntactic cues [e.g., ((honey mustard) (chicken burger))]. Contrasting sentences to word lists revealed a network that largely overlapped with the one reported in languages with rich morphosyntactic cues, including left IFGorb/IFGtri and areas along left STG/STS. Both conditions showed increased activation in left IFGtri/IFGorb in functional ROIs defined based on previous study in sentence processing, while the nominal phrases additionally revealed a constituent length effect in bilateral dorsal IFGtri, left IFGoper, left pMTG/pSTG, left IPL, and several subcortical areas, which might reflect an increased reliance on semantic and pragmatic information. Moreover, in upper left IFGtri/IFGoper and left thalamus/caudate, this effect increased with the participants' tendency to combine nouns into phrases. The absence of syntactic constraints on linguistic composition might highlight individual differences in cognitive control, which helps to integrate non-syntactic information.